Science and engineering of droplets : fundamentals and applications - Liu, Huimin, 1961- (Noyes Publications, 2000)
This is the first book to encompass the fundamental phenomenon, principles, and process of discrete droplets of both normal liquids ad melts. It provides the reader with the science and engeneering of discrete droplets, and provides researchers, scientists and engineers with the latest developments in the field.